Effects of a novel orally administered calpain inhibitor SNJ‐1945 on immunomodulation and neurodegeneration in a murine model of multiple sclerosis. (12th February 2014) - Trager, Nicole; Smith, Amena; Wallace IV, Gerald; Azuma, Mitsuyoshi; Inoue, Jun; Beeson, Craig; Haque, Azizul; Banik, Naren L.
Abstract Multiple sclerosis (MS) pathology is marked by the massive infiltration of myelin‐specific T cells into the CNS. Hallmarks of T helper (Th) cells during active disease are pro‐inflammatory Th1/Th17 cells that predominate over immunoregulatory Th2/Treg cells. Neurodegeneration, a major factor in progressive MS, is often overlooked when considering drug prescription. Here, we show that oral dosing with SNJ‐1945, a novel water‐soluble calpain inhibitor, reduces experimental autoimmune encephalomyelitis clinical scores in vivo and has a two pronged effect via anti‐inflammation and protection against neurodegeneration. We also show that SNJ‐1945 treatment down‐regulates Th1/Th17 inflammatory responses, and promotes regulatory T cells (Tregs) and myeloid‐derived suppressor cells in vivo, which are known to have the capacity to suppress helper as well as cytotoxic T cell functions. Through analysis of spinal cord samples, we show a reduction in calpain expression, decreased infiltration of inflammatory cells, and signs of inhibition of neurodegeneration. We also show a marked reduction in neuronal cell death in spinal cord (SC) sections. These results suggest that calpain inhibition attenuates experimental autoimmune encephalomyelitis pathology by reducing both inflammation and neurodegeneration, and could be used in clinical settings to augment the efficacy of standard immunomodulatory agents used to treat MS. <boxed-text content-type="graphic" id="jnc12659-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text> Multiple sclerosis (MS) pathology is marked by inflammation and infiltration of myelin‐specific T cells into the central nervous system. Inflammation leads to neurodegeneration in progressive MS which also leads to epitope spreading, feedback looping to more inflammation. Calpain can play a role in both arms of the disease. Here, oral dosing with SNJ‐1945, a novel water‐soluble calpain inhibitor, reduces experimental autoimmune encephalomyelitis clinical scores in vivo and has a two‐pronged effect via anti‐inflammation and protection against neurodegeneration.